Throughput enhancement in cognitive radio network via coalition formation using matching theory - Tahir, Mohammad; Habaebi, Mohamed Hadi; Islam, Md. Rafiqul (Institute of Electrical and Electronics Engineers, Inc., 2015)
Recently there have been numerous studies exploring the benefits of the coalition formation in a cognitive radio network and it has been shown that coalition formation tends to improve the performance of cognitive radios. In this paper, we use the concepts from matching theory to form coalitions among cognitive radio users for cooperative spectrum sensing under target detection probability constraint. In the proposed model we make use of one sided matching theory to develop an algorithm for the cognitive radios to form coalitions of varying size to improve their individual gains (.e.g. throughput and probability of false alarm). We show using simulations that the proposed matching algorithm for coalition formation yields significant gains in term of reduced false alarm probability and increased throughput per cognitive radio user as compared to non-cooperative scenario. Index Terms—cognitive radio; spectrum sensing; distributed algorithms; stable matching, matching theory.